Prosecution of Offenders in Liquid Fuels Turnover - Katarzyna, Paulina Simińska - Domańska (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The paper presents theoretical and practical aspects of prosecution of criminals involved in illegal sales of liquid fuels. It has been noticed that despite increasing attention paid to the prosecution of fuel frauds, the grey area still exists, which is due to the fact that such crimes are easy to commit, the profits to be gained are enormous, and legal consequences are rather insignificant. Recently, however, the detectability of tax frauds has increased. The improved efficiency of tax control authorities can be attributed to the introduction of the following: methodology of assessment of due diligence demonstrated by the buyers of goods in domestic transactions; JPK – the Polish equivalent of SAF-T (Standard Audit File for Tax); split payment; SENT system; fuel package.